MOTIVASI GAYA KEPEMIMPINAN DAN KOMITMEN ORGANISASI BERHUBUNGAN ERAT DENGAN KEPUASAN KERJA PERAWAT DI RUMAH SAKIT BHAYANGKARA POLDA D.I YOGYAKARTA - Supriyadi Supriyadi; Sendy Komarudin; Sri Nur Hartiningsih (STIKes Surya Global Yogyakarta, 2018)
Background: The quality of hospital services is strongly influenced by several factors, among which the most dominant factor is human resources. Human resources are the key to the success and success of the organization. Human resources related to the provision of health services in hospitals are nurses. managing human resources is not an easy thing because it involves many important factors that must be considered, one of which is the factor of job satisfaction. There are several indicators that must be considered by the hospital, one of which is to pay attention to the level of job satisfaction nurse (Simamora, 2012). Objective: This study aims to determine the relationship of motivation leadership style and organizational commitment with job satisfaction Nurse at Bhayangkara Hospital POLDA D.I. Yogyakarta. Methods: The research design used in this research is descriptive correlation research with cross sectional approach. Sampling technique with total sampling. Pupulation in this research is nurse counted 33 people. Bivariate statistical test using kendal tau while multivariate test using multiple linear regression with significant level 95%. Result: Result of research got all variable that is motivation, leadership style, and organizational commitment influence nurse job satisfaction with p value 0.001, 0.003, 0.000 (p0.05). Multivariate test obtained value of R 0.662 means the relationship between motivation, leadership style and organizational commitment with job satisfaction is strong. Conclusion: there is a relationship between motivation, leadership style and organizational commitment with job satisfaction